Species of the genus Salsola L. from the flora of the desert part of the Syrdarya river valley (conspectus and key to the definition) - B. B. Osmonali (Проблемы ботаники Южной Сибири и Монголии, 2021)
When various factors of human activity affect the environment, especially in areas located in the desert zone, the flora and vegetation of river floodplains, terraces, coastal strips and valleys are the most vulnerable. The anthropogenic impact in the Syrdarya river valley is characterized by a historical duration and significant intensity. First of all, this applies to floodplain landscapes, which have a number of features that must be taken into account when intensifying their economic use. They are very dynamic, easily vulnerable, subject to destruction by water, wind, various types of transport, intensive grazing of agricultural animals, etc. The family Chenopodiaceae Vent. is one of the largest and oldest families of the desert regions of Kazakhstan. In the family spectrum of the flora of the Syrdarya river valley, it occupies the first place in terms of the number of its representatives. A number of representatives of the family, being dominants and edi-fiers of many desert communities, play an important role in the composition of the vegetation cover, including with the participation (dominance) of species of the genus Salsola L. Classical botanical methods were used in the research process. According to the results of the research work, it was revealed that 17 species of the genus Salsola L., grouped in 5 sections, are found on the territory of the desert part of the Syrdarya river valley.